Urea assisted hydroxyapatite mineralization on MWCNT/CHI scaffolds - Hortigüela, María J. (2008)
Urea assisted hydroxyapatite (HAp) mineralization was performed on scaffolds composed of a major fraction of multiwall carbon nanotubes (MWCNT, 85 wt.%) and a minor one of chitosan (CHI, 15 wt.%). The MWCNT/CHI scaffolds were synthesized through a cryogenic process (so called ISISA, ice segregation induced self-assembly) that allowed the achievement of macroporous monoliths whose structure resembled a chamber-like architecture in the form of interconnected MWCNT/CHI sheets arranged in parallel layers crossed by pillars. The mineralized architectures were composed of flower like hydroxyapatite (HAp) crystalline clusters of ca. 1 mm, homogeneously distributed throughout the internal surface of the scaffold macrostructure. HAp mineralized MWCNT/CHI scaffolds were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR) and scanning and transmission electron microscopy (SEM and TEM, respectively). Calibrated energy dispersion X-ray spectroscopy (EDS) and selected-area electron diffraction (SAED) were also performed in the transmission electron microscope to further HAp characterization. Preliminary in vitro experiments demonstrated the suitability of HAp mineralized MWCNT/CHI scaffolds for bone tissue growth.